FILSAFAT YOGA Ashtānga-yoga Menurut Yoga-Sūtras Pātañjali - Matius Ali (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2010)
Abstract: What is Yoga? How is Self-realization achieved through Yoga? The great Sage Pātañjali (3rd Century B.C.) defined yoga in the Yoga-Sūtras as “the restraint of the modifications of the mind” (yogaś-citta-vritti-nirodah). In his Yoga-Sūtras (196 sutras), Pātañjali systematically laid down the exact methods and techniques for attaining Self-realization through the Eight Limbs of Pātañjali’s Yoga (Ashtānga-yoga). This system is commonly known as Rāja-yoga (Royal yoga). This Eight Steps is the way to attain self-transcendence. It consists of yama, niyama, āsanas, prānāyāma, pratyāhāra, dhāranā, dhyāna and samādhi. This article will focus on Ashtānga-yoga in the practical and philosophical contexts. Other systems of yoga also use this Eight Steps, but each yoga may start from and emphasize different aspects of yoga. However all systems of yoga accept and practice the Eight Steps of yoga to achieve the final goal, that is liberation (kaivalya, moksha, mukti). Yoga also reconciles the six systems of Indian Philosophy (Shadh Darśana). Keywords: Rāja-yoga (Royal yoga), Hatha-yoga (Hard yoga), Bhakti-yoga (Yoga of Devotion), Jñāna-yoga (Yoga of Knowledge), Ashtānga-yoga (Eight limbs of Yoga), Citta-vritti-nirodha (Restraint of modification of the mind), Purusha (Spirit), Prakriti (Matter), Iśvara-pranidhāna (Surrender to God), Moksha (Liberation).